1991
DOI: 10.1002/1097-0142(19911015)68:8<1685::aid-cncr2820680804>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the treatment of retinoblastoma in 72 patients

Abstract: Seventy‐two patients with retinoblastoma (RTB) (unilateral [47 patients] and bilateral [25 patients]) were studied for a period of 6 years. Treatment consisted of enucleation of those eyes that had severe involvement and was followed by radiation therapy and/or chemotherapy (systemic or intrathecal) according to clinical pathologic staging. All patients who underwent nonsurgical treatment received systemic chemotherapy. Intrathecal chemotherapy was administered when there was involvement of the central nervous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(14 citation statements)
references
References 18 publications
0
13
1
Order By: Relevance
“…Despite some reports of long term event free survival, 7-9 the bulk of the evidence suggests that the prognosis remains grim with such an approach. [10][11][12] Many centers have intensified chemotherapy with ASCR for malignancies, and two case reports have suggested that such an approach might be beneficial for patients with metastatic retinoblastoma. 13,14 Subsequently, Institut Curie investigators treated 25 patients with high risk retinoblastoma with high dose carboplatin, etoposide, and cyclophosphamide followed by ASCR.…”
Section: Discussioncontrasting
confidence: 53%
“…Despite some reports of long term event free survival, 7-9 the bulk of the evidence suggests that the prognosis remains grim with such an approach. [10][11][12] Many centers have intensified chemotherapy with ASCR for malignancies, and two case reports have suggested that such an approach might be beneficial for patients with metastatic retinoblastoma. 13,14 Subsequently, Institut Curie investigators treated 25 patients with high risk retinoblastoma with high dose carboplatin, etoposide, and cyclophosphamide followed by ASCR.…”
Section: Discussioncontrasting
confidence: 53%
“…The metastatic rate has ranged from 4% in a study of 26 cases in which vincristine sulfate and cyclophosphamide was used to 33% in a study of 24 cases in which vincristine sulfate, cyclophosphamide, and doxorubicin was used. 26,27 Mustafa and associates 30 studied the effect of vincristine sulfate, doxorubicin, and cyclophosphamide in high-risk RB and found distant metastasis and subsequent death in 19% cases. They concluded that alternative chemotherapeutic agents should be considered for patients with such high-risk features.…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant chemotherapy is not under discussion in these cases, as well as those with trans‐scleral invasion because a microscopic tumor residue is present. The traditional approach for the postenucleation treatment of these patients include adjuvant systemic and intrathecal chemotherapy along with radiotherapy 6, 9, 14, 38, 39. The survival rate for these patients ranged from 40% to 70% in such studies.…”
Section: Discussionmentioning
confidence: 99%